(untitled) (Revista Brasileira de Contabilidade e Gestão, 2012)
This document describes the operation of detection systems and intrusion prevention and the importance of deploying these tools on a network with access to the internet, highlighting a suitable tool for monitoring and access control and presenting the installation procedure with a basic configuration. Regarding the investment in security systems, it is known how important it is to protect yourself from malicious attacks that result in the theft of confidential data, denial of service, eavesdropping and modification of sites.